Diurnal Cortisol Secretion Is Not Related to Multiple Sclerosis-Related Fatigue - Malekzadeh, Arjan; Bader, Ilona; van Dieteren, Julia; Heijboer, Annemieke C.; Beckerman, Heleen; Twisk, Jos W. R.; de Groot, Vincent; Teunissen, Charlotte E. (Frontiers in Neurology, 2020)
Some evidence supports the involvement of the Hypothalamic-Pituitary-Adrenal axis (HPA-axis) with multiple sclerosis (MS)-related fatigue. In this study we determined the relation of HPA-axis function with primary fatigue in MS patients in the longitudinal Treating Fatigue in MS cohort. MS patients from the TREFAMS research program that consists of three Randomized Controlled Trials to study the effects of aerobic training (AT), energy conservation management (ECM) and cognitive behavioral therapy (CBT) on MS-related fatigue were included. At baseline, the end of treatment (16 weeks) and after 52 weeks, HPA-axis functioning was determined. The cortisol awakening response (CAR) and night time cortisol levels were analyzed. Fatigue was measured with the fatigue subscale of the Checklist Individual Strength (CIS20r fatigue). There was no relationship between CAR and night time cortisol parameters with CIS20r fatigue scores. Neither of the treatments influenced CAR and night time cortisol parameters, with the exception of an effect in the ECM treatment group on the CAR surge increase over 52 weeks (= -114.8, p= 0.007 95% CI= -197.6, -31.9). Our data suggest that HPA axis function is not associated with MS-related fatigue. This indicates that MS-related fatigue can not be attributed to HPA-axis dysfunction and is likely caused by other disease mechanisms.